Hyaluronic Acid Nanogels: A Promising Platform for Therapeutic and Theranostic Applications - Su Sundee Myint; Chavee Laomeephol; Sirikool Thamnium; Supakarn Chamni; Jittima Amie Luckanagul (MDPI AG, 2023)
Hyaluronic acid (HA) nanogels are a versatile class of nanomaterials with specific properties, such as biocompatibility, hygroscopicity, and biodegradability. HA nanogels exhibit excellent colloidal stability and high encapsulation capacity, making them promising tools for a wide range of biomedical applications. HA nanogels can be fabricated using various methods, including polyelectrolyte complexation, self-assembly, and chemical crosslinking. The fabrication parameters can be tailored to control the physicochemical properties of HA nanogels, such as size, shape, surface charge, and porosity, enabling the rational design of HA nanogels for specific applications. Stimulus-responsive nanogels are a type of HA nanogels that can respond to external stimuli, such as pH, temperature, enzyme, and redox potential. This property allows the controlled release of encapsulated therapeutic agents in response to specific physiological conditions. HA nanogels can be engineered to encapsulate a variety of therapeutic agents, such as conventional drugs, genes, and proteins. They can then be delivered to target tissues with high efficiency. HA nanogels are still under development, but they have the potential to become powerful tools for a wide range of theranostic or solely therapeutic applications, including anticancer therapy, gene therapy, drug delivery, and bioimaging.